'Evaluation that Empowers': A Model for Generating Evaluation-Minded Organisations. (September 2013) - Greenaway, Lesley
This article introduces the notion of 'Evaluation that Empowers' (EtE) as a model for generating 'evaluation-mindedness', which means to convey a deep and sustainable shift in organisational practice. The author developed the EtE Model through a literature review and a case study that involved examining evaluation practice in action. This article presents the initial findings from this research. What emerges is a framework for guiding evaluation practices that are participatory, empowering, sustainable and embedded.